Two new species of Xiphocentronidae (Trichoptera) and their bionomics in Central Amazonia, Brazil - Pes, Ana Maria; Hamada, Neusa; Nessimian, Jorge Luiz; Soares, Climéia C. (Zootaxa, 2013)
Two new Xiphocentronidae species are described, Machairocentron falciforme sp. nov. and Xiphocentron(Antillotrichia) sclerothrix sp. nov. Illustrations of the males, females and pupae are presented. Adults were obtained through the emergence of pupae in the laboratory and from collections in traps suspended 1 m above the water in four streams in Presidente Figueiredo, Manaus and Barcelos municipalities in Amazonas state, and Oiapoque municipality in Amapá state, Brazil. Larvae inhabiting submerged substrates and on stream banks were collected in order to determine thefeeding habits by examining gut contents. Larvae of both species are practically indistinguishable; the list of material observed in the gut content therefore refers to both species. Larvae of analyzed species have scraper feeding habits.